Health, human rights and freedom at stake? A critical discourse analysis of the Swedish media debate on the national COVID-19 pandemic strategy - Malin Hallén; Kristina Tryselius (International Journal of Qualitative Studies on Health & Well-Being)
Purpose The aim of this study is to, in the Swedish media debate, explore the discursive constructions of challenges in human rights and freedoms following the national spatial strategy for health and survival during the COVID-19 pandemic. Methods The study, inspired by a critical discourse analytic approach, focused particularly on the issues addressed, subject positions, relations and rhetoric. Seventeen opinion articles published in Swedish national newspapers December 2019 - February 2022 were analysed. Results The main contents were threats to democracy, threats to the freedom and rights of specific groups, and threats to the debate itself. Contents were expressed through three discourse dichotomies: contribution vs interjection, documented vs alarmistic, and active on the stage vs commenting from the balcony. Conclusions Striking about the results is the absence of dialogue, the one-way communication, and the absent politicians. It seems that the analysed debate on the challenges of the Swedish COVID-19 pandemic strategy, based on its impact on overall freedoms and rights, has not been the focus of decision-makers during the pandemic. They have neither addressed the threats highlighted in the articles, nor contributed to the discourse. This is worrying for the long-term maintenance and development of a healthy democracy.